(untitled) (REMUNOM, 2025)
This article aims to analyze the role of teaching Plane Geometry in the development of mathematical literacy among 9th-grade students in a public school. The research adopted a qualitative approach, including a literature review and the implementation of pedagogical activities based on concrete materials and mathematical modeling. The study involved diagnostic and final tests, observations, and questionnaires to assess students’ levels of mathematical literacy and their perceptions of Geometry instruction. The results indicate that pedagogical practices incorporating concrete resources and modeling strategies significantly contribute to students’ understanding and application of geometric concepts, leading to improved problem-solving performance. In conclusion, the study reinforces the importance of Geometry in the process of mathematical literacy and highlights the need for more contextualized and meaningful teaching methodologies.